IMPLEMENTASI PROGRAM KARTU INDONESIA PINTAR KULIAH MERDEKA DI UNIVERSITAS SULTAN AGENG TIRTAYASA - Nurul Fahmi Tubagus; Titi Stiawati (NIAGARA Scientific Journal, 2023)
The Indonesia Smart Card for Merdeka College (KIP-Kuliah Merdeka) is one of the Smart Indonesia programs during the administration of President Joko Widodo through the Ministry of Education and Culture in the form of cash assistance, expanding access and learning opportunities provided to students with poor or vulnerable family backgrounds in throughout Indonesia to finance education. This research was conducted to find out the Implementation of the KIP-Independence College Program at Sultan Ageng TirtayasaUniversity (UNTIRTA), because in its implementation there were several issues which stated that the KIP-Independence College program was not on target, the schedule for disbursing pocket money and the KRS process was delayed, and there was a lack of transparency for students receiving the KIP-Kuliah Merdeka Replacement scholarship. In order to answer these issues, researchers used the theory of Policy Implementation from George C Edward III with its four indicators namely Communication, Resources, Disposition, and Bureaucratic Structure using a Descriptive Qualitative research method. The research findings in this research are that the implementation of the KIP-Kuliah Merdeka program has been carried out well, starting from a very strict selection process, students who are substitutes for KIP-Kuliah scholarship recipients are students who previously nominated themselves but did not pass, as well as those who become obstacles to the process disbursement of pocket money and the KRS process are students who arelate in filling out the re-registration that has been requested previously